Standar Prosedur Operasional Pemberian Traksi Oscilasi Pada Pasien Dengan Frozen Shoulder. Tugas Akhir thesis, Universitas Muhammadiyah Surakarta. - Triyana, Triyana (2015)
Physiotherapy management of the pathology Frozen Shoulder still found many differences, though following the same general pattern. To equate the same perception on the handling of pathology Frozen Shoulder necessary to standard operating procedures. Giving Traction Oscilasi in patients with Frozen Shoulder is one of the effective methods of treatment of physiotherapy. The existence of operational standards will make it easier to take action.